The Southern Ocean Time Series: a climatological view of hydrography, biogeochemistry, phytoplankton community composition, and carbon export in the Subantarctic Zone - E. H. Shadwick; E. H. Shadwick; C. A. Wynn-Edwards; C. A. Wynn-Edwards; R. S. Eriksen; R. S. Eriksen; R. S. Eriksen; R. S. Eriksen; P. Jansen; X. Yang; X. Yang; G. Woodward; et al. (Ocean Science)
The Southern Ocean Time Series (SOTS) provides highly temporally resolved observations of the physical, chemical, and biological variability in the upper ocean, as well as the export of particulate organic and inorganic carbon to the ocean interior, in the subantarctic region south of Australia. The SOTS observatory focuses on the subantarctic region because of its importance in the formation of mode water and the associated uptake and storage of anthropogenic heat and carbon. The region is also critical for the supply of oxygen to the ocean interior and the export of nutrients to fuel primary production in broad areas of the low-latitude global ocean. The SOTS observatory is the longest running multidisciplinary initiative in the open Southern Ocean and has delivered high-quality observations from the surface to the seafloor for more than a decade and, for some parameters, for over two decades, using two deep-water moorings. The moorings are serviced annually, providing additional opportunities for shipboard sampling and sensor validation and calibration. Using observations collected at the SOTS site between 1997 and 2022, we present the seasonal variability in upper-ocean hydrography, biogeochemistry, phytoplankton and microplankton community composition, and diversity, along with particulate organic and particulate inorganic carbon export to the deep ocean. This climatological view of the region is complemented by a review of recent findings underpinned by observations collected by the SOTS observatory and highlighting the ongoing need for long time series to better understand the Subantarctic Ocean and its response to a changing climate.